2021
DOI: 10.1037/hea0001101
|View full text |Cite
|
Sign up to set email alerts
|

Translating strategies for promoting engagement in mobile health: A proof-of-concept microrandomized trial.

Abstract: Objective: Mobile technologies allow for accessible and cost-effective health monitoring and intervention delivery. Despite these advantages, mobile health (mHealth) engagement is often insufficient. While monetary incentives may increase engagement, they can backfire, dampening intrinsic motivations and undermining intervention scalability. Theories from psychology and behavioral economics suggest useful nonmonetary strategies for promoting engagement; however, examinations of the applicability of these strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 76 publications
1
30
0
Order By: Relevance
“…However, digital stimuli used to promote engagement in digital interventions are not limited to nudges. For example, monetary incentives for a specific option do not qualify as nudges (Campos-Mercade et al, 2021), but are sometimes used to promote engagement in digital interventions (Nahum-Shani, Rabbi, et al, 2021). Further, nudging typically seeks to bypass consciousness, deliberation, and reasoning, but digital stimuli for promoting engagement in digital interventions may require deep and lengthy thinking, as they sometimes offer useful information about the person’s behavior and context to facilitate self-reflection (Bidargaddi et al, 2018; Rabbi et al, 2018).…”
Section: Engagement In Digital Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, digital stimuli used to promote engagement in digital interventions are not limited to nudges. For example, monetary incentives for a specific option do not qualify as nudges (Campos-Mercade et al, 2021), but are sometimes used to promote engagement in digital interventions (Nahum-Shani, Rabbi, et al, 2021). Further, nudging typically seeks to bypass consciousness, deliberation, and reasoning, but digital stimuli for promoting engagement in digital interventions may require deep and lengthy thinking, as they sometimes offer useful information about the person’s behavior and context to facilitate self-reflection (Bidargaddi et al, 2018; Rabbi et al, 2018).…”
Section: Engagement In Digital Interventionsmentioning
confidence: 99%
“…Although low engagement has been consistently cited as the construct underlying these phenomena (e.g., Chien et al, 2020; Pratap et al, 2020), there has been limited theoretical and empirical work to understand how engagement in digital interventions unfolds. Further, the notion of engagement plays a critical role in various domains of psychology, including occupational (Bakker & van Wingerden, 2021), clinical (Georgeson et al, 2020), educational (Reinke et al, 2019), and health psychology (Nahum-Shani, Rabbi, et al, 2021). However, there is a disagreement about the definition of this construct across and within various fields, and it is often unclear how engagement is different from other related constructs, making it difficult to ascertain its scientific value.…”
mentioning
confidence: 99%
“…Advances in mobile and wireless technology can be used to increase the convenience and accessibility of self-monitoring tools (Bidargaddi et al, 2018; Rabbi et al, 2018). Yet, engagement (i.e., energy invested in a focal task or stimulus; Nahum-Shani et al, 2022) with digital tools remains a critical barrier as individuals abandon digital self-monitoring quickly and after minimal use (Nahum-Shani et al, 2021). For example, a recent systematic review of digital self-monitoring in weight loss interventions found modest engagement in digital self-monitoring, with very few interventions meeting an average threshold of 75% completion (Patel et al, 2021).…”
Section: Self-monitoring Of Alcohol Use In An Adaptive Preventive Int...mentioning
confidence: 99%
“…Bonar et al, 2018; Dworkin et al, 2017). Importantly, studies that explicitly focused on repeated assessments of alcohol use (e.g., every week or several weeks) either employed financial incentives that are not guaranteed (e.g., a prize draw to win a £25 voucher; Bewick et al, 2010) and achieved relatively low (e.g., less than 65%) completion rates, or yielded higher completion rates (e.g., 75%–86%) by combining minimal guaranteed incentives (e.g., $.50, $2) with relatively high completion-based bonuses (e.g., an extra $20 each semester for completing the majority of assessments; Barnett et al, 2015) or human support to encourage completion, which is both costly and complex to implement (Nahum-Shani et al, 2021). Thus, an important question is whether and how self-relevance can be leveraged to increase the perceived value of self-monitoring when only relatively minimal financial incentives are provided.…”
Section: Self-monitoring Of Alcohol Use In An Adaptive Preventive Int...mentioning
confidence: 99%
“…Although advances in mobile and wireless technology offer tremendous potential for delivering JITAIs, researchers often need more empirical evidence to inform the selection and adaptation of components in a JITAI, and these knowledge gaps can motivate scientific questions for randomized studies [e.g., (47)(48)(49)]. Consider Example D discussed above and suppose there is not yet sufficient evidence to determine (a) whether delivering a prompt that recommends a brief self-regulatory strategy is beneficial on average in preventing a lapse in the next 3 h, when individuals are not driving; and (b) what is the level of urge at which the prompt would be most beneficial.…”
Section: Rapidly: Components Address Conditions That Change Rapidlymentioning
confidence: 99%